Elective pelvic nodal irradiation for elderly patients with high-risk prostate cancer: A more patient-oriented approach - Federico Iori; Matteo Augugliaro; Emanuele Alì; Cinzia Iotti (Clinical and Translational Radiation Oncology)
The role of elective pelvic nodal irradiation (EPNI) for high-risk prostate cancer (hrPC) management is still an open issue, especially for the elderly patients. It is unclear whether older patients can experience the same benefit from the treatment strategies used for younger men. Hence, in absence of solid data, it appears reasonable to pursuit a shared decision-making process so that older patients can express their informed preferences about the different treatment options. In this letter, we discuss why caution appears reasonable on EPNI trade-off in hrPC patients aged 75 years or more.